Математичне моделювання в аналізі дерегульованого енергетичного ринку - Монтицька, А. М. (Видавництво Національного університету «Львівська політехніка», 2003)
На основі світового досвіду досліджено, чому і як сформовані енергетичні пули, аналізуються різні типи контрактів з і без доступу до методів спотового ринку. Для аналізу роботи енергетики у нових умовах ми використовуємо методи оптимізації та моделювання. In this paper on the basis of world experience we discuss why and how power pools are formed, and analyse management of different types of pools with and without access to spot market instruments. The market of the electric power in Ukraine develops. Successful business in this new, more volatile market requires sophisticated techniques for identifying new market opportunities and managing the increased risks. For the analysis of work of a power engineering in new conditions we use simulation and optimisation techniques.